Design of Compact Microstrip U Shape Bandpass Filter Using Via Ground Holes - Fajri Darwis; Arief Budi Santiko; Novita Dwi Susanti (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
This paper present the microstrip bandpass filter using two U shape resonators with using via ground holes. The bandpass filter was established using two U shape resonators with using via ground holes and deployed on RT/duroid 6010 LM aims to minimize the dimension of filter. The proposed filter was characterized using software simulation. The characteristic of proposed filter is to deal with required specification. Hardware realization was done to verify the characteristic of proposed filter. The bandpass filter has the dimension of 4.2 mm x 3.8 mm. The filter was expected to have center frequency of 400 Mhz with minimum 3dB bandwidth of 15 Mhz, maximum insertion loss of -1.5 dB and VSWR less than 2. VSWR and 3dB bandwidth on realized filter have a good agreement with required specification. However the insertion loss and center frequency was not adequate. The realized filter has insertion loss of -2.554 dB with the center frequency of 404.711 MHz.